Electrokinetics of charged spherical colloidal particles taking into account the effect of ion size constraints - López García, José Juan (2011)
The electrokinetic properties of suspended spherical particles are examined using a modified standard electrokinetic model, which takes into account the finite ion size and considers that the minimum approach distance of ions to the particle surface need not be equal to their effective radius in the bulk solution. We calculate the conductivity increment and the electrophoretic mobility and present a detailed interpretation of the obtained results, based on the analysis of the equilibrium and field-induced ion concentrations, as well as the convective fluid flow in the neighborhood of the particle surface. We show that when charge reversal takes place, the sign of the concentration polarization remains unchanged while the sign of the electrophoretic mobility only changes under favorable circumstances.